Climate-induced population displacement in sub-Saharan Africa: A review of resilience-building strategies. Issue 117 (December 2020) - Graham, Christopher
Highlights: Climate change is inducing population displacement in parts of sub-Saharan Africa. Resilience-building projects implemented at different scales are helping to mitigate population displacement. Climate Smart Agriculture (CSA) is expanding food and economic security. Enhanced data and measurement capabilities are being used to assess structural vulnerabilities. Early Warning Systems (EWS) are enhancing climate planning and predictability. Abstract: Growing evidence suggests that there is a correlation between climate change and increasing levels of human population displacement in sub-Saharan Africa. Over the last two decades, stakeholders have established various resilience-building programs to mitigate climate disaster risks and their adverse impacts on life and livelihoods across the region. These programs have focused on enhancing food and water security while expanding the capacity to predict and plan for climate disasters. Despite a growing body of research, the role of climate resilience-building strategies in mitigating climate-induced displacement has received relatively little attention. This paper contributes to filling this salient gap in the scholarly and policy discourse on this issue. Sub-Saharan Africa is used in this paper as an example that represents a region comprised of developing countries experiencing a variety of climate-induced challenges. Sub-Saharan Africa also has been an incubator for a variety of experimental strategies implemented at the community, national and regional levels to respond to climate shocks and reduce climate risks. Using an integrated resilience building approach that prioritizes understanding vulnerabilities and structural needs in response to climate challenges, this paper examines key strategies implemented in sub-Saharan Africa to reduce the climate risks that have the greatest consequences for population displacement.